1999
DOI: 10.1016/s0006-3495(99)77486-2
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Diffusion of Major Histocompatibility Complex Class I Molecules on HeLa Cells Determined by Single Particle Tracking

Abstract: Single-particle tracking (SPT) was used to determine the mobility characteristics of MHC (major histocompatibility complex) class I molecules at the surface of HeLa cells at 22 degrees C and on different time scales. MHC class I was labeled using the Fab fragment of a monoclonal antibody (W6/32), covalently bound to either R-phycoerythrin or fluorescent microspheres, and the particles were tracked using high-sensitivity fluorescence imaging. Analysis of the data for a fixed time interval suggests a reasonable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
128
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 68 publications
(84 reference statements)
9
128
0
Order By: Relevance
“…1 also is not appropriate when the population contains different mobility fractions. Such heterogeneous populations can be analyzed much better and the mobility modes dissected to a certain degree by an analysis of jump-distance distributions (34,43,44). In this type of analysis, the probability p(r, t)dr that a particle starting at the origin will be encountered within a shell of radius r and a width dr at time t is considered.…”
Section: The Quantitative Analysis Of U1 Snrnp Trajectories Suggests mentioning
confidence: 99%
“…1 also is not appropriate when the population contains different mobility fractions. Such heterogeneous populations can be analyzed much better and the mobility modes dissected to a certain degree by an analysis of jump-distance distributions (34,43,44). In this type of analysis, the probability p(r, t)dr that a particle starting at the origin will be encountered within a shell of radius r and a width dr at time t is considered.…”
Section: The Quantitative Analysis Of U1 Snrnp Trajectories Suggests mentioning
confidence: 99%
“…In particular, living cells provide striking examples for systems where subdiffusion has been repeatedly observed experimentally, either in the cytoplasm (6)(7)(8)(9), the nucleus (10,11), or the plasmic membrane (12)(13)(14). However, the microscopic origin of subdiffusion in cells is still debated, even if believed to be caused by crowding effects in a wide sense, as indicated by in vitro experiments (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Studies using single particle tracking (SPT) showed mobile MHC I molecules following anomalous diffusion (i.e. nonlinear time dependence) over time scales of 100 ms to 300 s or transient confinements within domains of various sizes (13)(14)(15)(16). The lateral diffusion of MHC-I molecules in plasma membranes was increased upon truncation of their cytoplasmic tail or replacement of their transmembrane and intracellular portions with a glycosylphosphatidylinositol (GPI) anchor (12,16).…”
mentioning
confidence: 99%